Prevention of Burn Wound Progression by Mesenchymal Stem Cell Transplantation: Deeper Insights Into Underlying Mechanisms - Abbas, Ozan Luay; Özatik, Orhan; Gönen, Zeynep Burçin; Öğüt, Serdal; Entok, Emre; Özatik, Fikriye Yasemin; Bahar, Dilek; Bakir, Zehra Burcu; Musmul, Ahmet (Annals of plastic surgery, 2018)
Burns are dynamic wounds that may present a progressive expansion of necrosis into the initially viable zone of stasis. Therefore, salvage of this zone is a major subject of focus in burn research. The beneficial effects of mesenchymal stem cells (MSCs) on the survival of the zone of stasis have been previously documented. However, many gaps still exist in our knowledge regarding the underlying protective mechanisms. Hence, this study was designed to evaluate the pathophysiological basis of MSCs in the prevention of burn wound progression. Wistar rats received thermal trauma on the back according to the "comb burn" model. Animals were randomly divided into sham, control, and stem cell groups with sacrifice and analysis at 72 hours after the burn. The stasis zones were evaluated using histochemistry, immunohistochemistry, biochemistry, real-time polymerase chain reaction assay, and scintigraphy to evaluate the underlying mechanisms. Gross evaluation of burn wounds revealed that vital tissue percentage of the zone of stasis was significantly higher in the stem cell group. Semiquantitative grading of the histopathologic findings showed that MSCs alleviated burn-induced histomorphological alterations in the zone of stasis. According to CC3a staining and expression analysis of Bax (B-cell leukemia 2-associated X) and Bcl-2 (B-cell leukemia 2) genes, MSCs attenuated increases in apoptosis postburn. In addition, these transplants showed an immunomodulatory effect that involves reduced neutrophilic infiltration, down-regulation of proinflammatory cytokines (tumor necrosis factor α, interleukin 1β [IL-1β], and IL-6), and up-regulation of the anti-inflammatory cytokine IL-10 in the zone of stasis. Burn-induced oxidative stress was significantly relieved with MSCs, as shown by increased levels of malondialdehyde, whereas the expression and activity of the antioxidant enzyme superoxide dismutase were increased. Finally, MSC-treated interspaces had enhanced vascular density with higher expression levels for vascular endothelial growth factor A, platelet-derived growth factor, fibroblast growth factor, and transforming growth factor β. Gamma camera images documented better tissue perfusion in animals treated with MSCs. The protective effects of MSCs are mediated by the inhibition of apoptosis through immunomodulatory, antioxidative, and angiogenic actions.